Ocean pressure data measured beneath the Ross Ice Shelf responding to the 2022 Hunga Tonga–Hunga Haʻapai tsunami ... - Stewart, Craig; Horgan, Huw; Stevens, Craig (SEANOE, 2022)
On the 15 January 2022, the volcano Hunga Tonga–Hunga Ha'apai in the southwest Pacific Ocean (20°32'32.37"S 175°23'38.67"W) erupted in what proved to be the most powerful such event since Krakatau in 1883. Among the many impacts of the eruption, a substantial tsunami propagated throughout the southwest Pacific Ocean. The signatures of the eruption were recorded at a wide range of recording stations globally including the atmospheric pressure wave, the tsunami itself and in addition, higher order responses such as a tsunami associated with the pressure wave. Here we describe what is likely the most southerly oceanic measurement of the tsunami arrival as the event was detected in a sub-ice mooring at the grounding line of the Ross Ice Shelf at 82.47 o South. It was recorded on the margin of the Ross Ice Shelf along the Siple Coast at the KIS2 (Kamb Ice Stream 2) field camp by instruments deployed to record ice-ocean interactions in order to improve understand ocean effects on ice sheet stability. The data were ...